AN ANTIBIOTIC-RESISTANCE ENZYME FROM A DEEP-SEA BACTERIUM - Toth, Marta (2010)
We describe herein a highly proficient class A β-lactamase OIH-1 from the bacterium Oceanobacillus iheyensis, whose habitat is the sediment at a depth of 1050 meters in the Pacific Ocean. The OIH-1 structure was solved by molecular replacement and refined at 1.25 Å resolution. OIH-1 has evolved to be an extremely halotolerant β-lactamase capable of hydrolyzing its substrates in the presence of NaCl at saturating concentration. Not only is this the most highly halotolerant bacterial enzyme structure known to date, it is also the highest resolution halophilic protein structure yet determined. Evolution of OIH-1 in the salinity of the ocean has resulted in a molecular surface that is coated with acidic residues, a marked difference with β-lactamases of terrestrial sources. OIH-1 is the first example of an antibiotic-resistance enzyme that has evolved in the depths of the ocean in isolation from clinical selection and gives us an extraordinary glimpse into protein evolution under extreme conditions. It represents evidence for the existence of a reservoir of antibiotic-resistance enzymes in nature among microbial populations from deep oceanic sources.